C3H6/C3H8 Adsorption Behavior Study of Stiffened ZIF‐8 Prepared under an Electric Field - Lyu, Luxi; Wu, Houxiao; Li, Libo; Wei, Yanying; Wang, Haihui (Chemie ingenieur technik, 2022)
Metal‐organic frameworks (MOFs) show great potential for adsorption separation. However, MOFs' flexibility may influence their adsorption behaviors. Here, for the first time we prepare ZIF‐8 powder dominated with stiffened ZIF‐8_Cm phase under an external E‐field. By comparison, we find that the flexibility of ZIF‐8 has little influence in equilibrium‐based separation behavior for C3H6/C3H8. However, the stiffened ZIF‐8 formed in E‐field presents an obviously decreased diffusion rate for C3H8, whose C3H6/C3H8 kinetic‐based separation factor is around 2.5 times higher than that of the traditional ZIF‐8 powder. ZIF‐8 was synthesized with an external electric field. It was found that it has more stiffened phase compared to traditional ZIF‐8. Adsorption experiments showed that the flexibility of ZIF‐8 influences its gas adsorption/separation performance especially for C3H6/C3H8 kinetic‐based separation.